1998
DOI: 10.1073/pnas.95.10.5568
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 complements defects in an interferon-resistant cell line: Evidence for an essential role for STAT3 in interferon signaling and biological activities

Abstract: STAT proteins play critical roles in the signal transduction pathways for various cytokines. The type I interferons (IFN␣͞␤) promote the DNA-binding activity of the transcription factors STAT1, STAT2, and STAT3. Although the requirement for STAT1 and STAT2 in IFN␣͞␤ signaling and action is well documented, the biological importance of STAT3 to IFN action has not yet been addressed. We found that STAT3 plays a critical role in signal transduction by IFN␣͞␤. A human cell line that is resistant to the antiviral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 39 publications
7
95
0
1
Order By: Relevance
“…Among the STAT proteins, STAT1 appears to play a key role in IFN-␣ signaling, 30 although STAT3 has also been implicated in mediating IFN-␣ activity in other studies. [31][32][33][34] Our study demonstrated that STAT3, not STAT1, was significantly activated by IFN-␣ at the concentrations (50 U or 100 U/mL) that show antiviral activity. The phosphorylated STAT1 did not respond to up to 100 U/mL IFN-␣ treatment, although it did so at 500 U/mL, a relatively higher concentration for antiviral effect in this model.…”
Section: Discussionmentioning
confidence: 91%
“…Among the STAT proteins, STAT1 appears to play a key role in IFN-␣ signaling, 30 although STAT3 has also been implicated in mediating IFN-␣ activity in other studies. [31][32][33][34] Our study demonstrated that STAT3, not STAT1, was significantly activated by IFN-␣ at the concentrations (50 U or 100 U/mL) that show antiviral activity. The phosphorylated STAT1 did not respond to up to 100 U/mL IFN-␣ treatment, although it did so at 500 U/mL, a relatively higher concentration for antiviral effect in this model.…”
Section: Discussionmentioning
confidence: 91%
“…As an alternative approach, our laboratory has resorted to long term IFN treatment of cells to isolate naturally arising IFN-resistant mutants, which more closely resemble what occurs in vivo (10,11). Using this strategy, we previously identified a STAT3-defective IFN-resistant cell line (11).…”
Section: Ifnmentioning
confidence: 99%
“…IFN signals through the activation of the IFN-stimulated gene factor 3 (ISGF3) complex, composed of STAT1, STAT2, and IRF9 (17), as well as STAT1 and STAT3 dimers that bind to ISG promoter elements (11). As shown in Fig.…”
Section: Characterization Of Ifn-resistant Rst2mentioning
confidence: 99%
See 2 more Smart Citations